Dual-nature biometric recognition epitome - Shahzad Ashraf; Tauqeer Ahmed (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
All humans are born with unique physically identified body characteristics to other persons which remains unchanged throughout life. These characteristics are taken into account by the emerging technology to get recognized from person to person. The technology used by the traditional human identification system sometimes becomes inefficient when data or images received are not up to the acceptable quality mark or when a person has a face covered with mask-like during epidemic virus fistula. In order to overcome such human recognition challenges, a Multi-biometric sustainable approach (D-nb) has been proposed using two uniquely identified modalities like foot and iris. This approach shrewdly identifies and makes the bodacious recognition among humans and suggests the sagacious result which is foremost better than the traditional biometric system.